2015
DOI: 10.12659/ajcr.895566
|View full text |Cite
|
Sign up to set email alerts
|

Pin Worms Presenting as Suspected Crohn’s Disease

Abstract: Patient: Female, 24Final Diagnosis: Pinworms infectionSymptoms: Abdominal pain • bloatingMedication: —Clinical Procedure: Colonoscopy and biopsySpecialty: Gastroenterology and HepatologyObjective:Rare diseaseBackground:Inflammatory bowel disease (IBD) is well recognized in developed countries and is generally among the differential diagnoses of young patients presenting with refractory diarrhea once other more common etiologies have been excluded. Pinworm infections, on the other hand, are not as common among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Al-Saffar et al reported a 24-year-old female diagnosed with appendicitis with a link to an active case of E vermicularis with eosinophilia. 11 Another report by de Jong et al described a 32-year-old woman with chronic diarrhea found to have eosinophilic infiltration of her colonic mucosa as well as peripheral eosinophilia attributed to enterobiasis. 12 These 2 cases, although of adult patients, demonstrate a potential causal link between eosinophilia and pinworm infections.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Saffar et al reported a 24-year-old female diagnosed with appendicitis with a link to an active case of E vermicularis with eosinophilia. 11 Another report by de Jong et al described a 32-year-old woman with chronic diarrhea found to have eosinophilic infiltration of her colonic mucosa as well as peripheral eosinophilia attributed to enterobiasis. 12 These 2 cases, although of adult patients, demonstrate a potential causal link between eosinophilia and pinworm infections.…”
Section: Discussionmentioning
confidence: 99%